Validation of the Academic School Climate Scale for Students - Spring, Crystal; Ochoa, Andrea (Journal of psychoeducational assessment, 2024)
This study sought to develop an Academic School Climate Scale measuring students’ perceptions of the learning environments at their schools. With a pilot sample of 1,265 students and validation sample of 14,773 students in Grades 4–12 in schools across the U.S., results of EFA and CFA supported a bifactor model with a general factor and three subscales: High Standards, Teacher Support of Student Learning, and Peer Support of Learning. We found scalar invariance by gender and race, and metric invariance by grade band. Correlations of the Academic School Climate Scale with open classroom climate and school climate indicated concurrent validity.